The Meeting of Myths and Realities: The “Homecoming” of Second-Generation Exiles in Post-Apartheid South Africa - De Sas Kropiwnicki, Zosa Olenka (Refuge: Canada's Journal on Refugees, 2014)
This article is based on the findings of a qualitative study of second-generation exiles, who were born in exile and/or spent their formative years in exile during apartheid. It is based on in-depth interviews with forty-seven men and women who spent their childhoods in North America, Western Europe, Eastern Europe, West Africa, East Africa, and southern Africa as second-generation exiles during apartheid. This article will focus on the tensions that arose over the myths and realities of return, in what often became dashed expectations of returning to a welcoming, free, and progressive post-apartheid South Africa, politically and socially united around key liberation principles. It will also discuss the manner in which the experience and memory of exile influenced former second-generation exiles’ perceptions of their roles as agents of change in post- apartheid South Africa—roles that were often adopted in the name of an ongoing liberation struggle.